Genetic characteristics of group A rotaviruses circulating in the Orenburg region during various epidemic seasons - N. B. Denisyuk (Журнал инфектологии, 2021)
Objective. To analyze the genetic structure of rotaviruses of group A, circulating on the territory of the Orenburg region in different epidemic seasons.Materials and methods: The genetic structure of rotaviruses by G/P alleles was determined in 341 fecal samples of patients with gastroenteritis clinic under the age of 5 years in various epidemic seasons. ELISA and PCR methods were used. The typing of rotaviruses was conducted on the basis of the laboratory of molecular diagnostic and epidemiology of enteric infections of the Department molecular diagnostics Central research Institute of epidemiology.Results: The general genetic structure of group a rotaviruses circulating in the Orenburg region in the period from 2014—2020 was determined, expressed, by the frequencies of G/P alleles. The genetic potential of group a rotaviruses for the entire study period was represented by twelve variants of genotypes for G/P alleles, the leading role in the epidemic process was played by genotypes with the highest frequency of occurrence: G4[P]8, G9[P]8, G2[P]4, Mixt. The frequency of registration of combined forms of various rotavirus genotypes (Mixed forms) was 5,9%.Conclusion: The main and dominant genotypes, their regional diversity and inter-seasonal fluctuations are established. The spectrum of circulating rotavirus genotypes differed in different epidemic seasons, and their epidemic significance is shown.